Pengaruh Emosional, Spiritual dan Adversity Quotien terhadap Self Control dan Self Succes Siswa di MA Muhammadiyah 02 Pondok Modern Paciran Lamongan - Khoirul Zikiyama (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
MA Muhammadiyah 02 Modern Boarding School Paciran indicates efforts to develop emotional, spiritual and adversity quotient on students through Madrasah learning activities. Students can develop their potential as they get older so that they are able to achieve optimal self-control and self-success. The formulation of the problem, First, How is the emotional influence on students' self-control and self-success, Second, How is the spiritual influence on students' self-control and self-success, Third, How is the Adversity quotient influence on students' self-control and self-success, Fourth, How is the emotional, spiritual, and Adversity quotient influence on students' self control and self success This type of research is quantitative research using validity, reliability, normality and homogeneity tests with simple regression analysis techniques and multiple regression. The results of the problem formulation can be concluded that: (1) There is a significant influence of emotional intelligence on students' self control and self success. (2) There is an influence of spiritual intelligence on students' self control and self success. (3) There is an influence of adversity quotient intelligence on students' self control and self success. (4) There is an influence of emotional, spiritual, and adversity quotient intelligent on students' self control and self success. MA Muhammadiyah 02 Pondok Modern Paciran mengindikasikan upaya dalam menumbuh kembangkan kecerdasan emosional, spiritual dan adversity pada peserta didik dengan melalui kegiatan pembelajaran Madrasah. Siswa dapat mengembangkan potensi diri seiring bertambah usia sehingga mampu mencapai self control dan self success secara optimal. Rumusan masalah, Pertama, Bagaimana pengaruh emosional terhadap self control dan self success siswa, Kedua, Bagaimana pengaruh spiritual terhadap self control dan self success siswa , Ketiga, Bagaimana pengaruh Adversity quotient terhadap self control dan self success siswa, Keempat, Bagaimana pengaruh emosional, spiritual dan Adversity quotient terhadap self control dan self success siswa. Jenis penelitian ini adalah penelitian kuantitatif menggunakan uji validitas, reliabilitas, normalitas dan homogenitas dengan teknik analisis regresi sederhana dan regresi ganda. Hasil dari rumusan masalah dapat disimpulkan bahwa : (1) Ada pengaruh yang signifikan dari kecerdasan emosional terhadap self control dan self success siswa. (2) Ada pengaruh kecerdasan spiritual terhadap self control dan self success siswa. (3) Ada pengaruh kecerdasan adversity quotient terhadap self control dan self success siswa. (4) Ada pengaruh kecerdasan emosional, spiritual dan adversity quotient terhadap self control dan self success siswa.